Juror adjustments to the reasonable doubt standard of proof. Issue 6 (2nd July 2016) - Park, Kwangbai; Seong, Yoori; Kim, Minchi; Kim, JongHan
ABSTRACT: The standard of proof beyond a reasonable doubt is based on the law's primary motivation to avoid false conviction even at the expense of increasing the probability of false acquittal. Individual jurors, however, have common sense motivations to make factually correct decisions by avoiding both types of error. As a result jurors may interpret the standard of reasonable doubt correctly but deviate from that interpretation in predictable ways when they apply the standard in court. This study makes three hypotheses: (1) jurors are less confident when deciding on acquittal than when deciding upon conviction, (2) conviction is associated with a downward adjustment of the interpreted stringency of the standard at the time of application, and (3) a highly stringent interpretation of the standard is associated with a severe downward adjustment of that stringency at the time of application. The study asked 260 juror-eligible participants to examine a trial scenario. The participants first interpreted the stringency of the legal standard on a probability scale. They then judged the probability of the defendant's guilt, decided on a verdict, and rated their confidence in that verdict. The findings strongly supported all three hypotheses. Application and implication of the study were discussed.